Implementation of History Learning Planning Study of Interest and Understanding of History in Students - Muthohharoh, Muthohharoh (Indonesian Journal of History Education, 2018)
A well-crafted learning plan is indispensable in the study of history, given its profound impact on shaping our understanding of the past and influencing our perspectives on the present and future. This article explores the methodologies employed by history educators in devising and executing their lesson plans, focusing on how these strategies influence students' sustained interest in historical narratives and deepen their grasp of intricate historical concepts. By meticulously planning and implementing effective teaching practices, educators can adeptly navigate the complexities of history education, ensuring the attainment of educational objectives. Central to this achievement is students' active engagement and enhanced comprehension of historical contexts, which are pivotal in fostering a meaningful learning process. Research conducted in the Rembang district underscores the efficacy of history teachers' pedagogical approaches, emphasizing their ability to develop engaging lesson plans that resonate with students and facilitate enriching learning experiences.